Law as a sign of Aragon’s identity. Aragonese Civil Law past, present and future: a more European Law - Bayod López, Carmen (Revista de derecho aragonés, 2024)
This paper analyses from the present, the evolution of Aragonese Foral Law until the present day although with a threefold approach: the Law as a sign of identity of Aragon, an official truth that is confirmed from the text of Fueros de Aragón; the survival of this Law and its influence on the current legislative plurality, examining the relations between Spanish State Law and Aragonese Law and, at last, the situation of Aragonese Civil Law in the European context.